FLORAE MALESIANAE PRAECURSORES XLVII. CENSUS OF MALESIAN CASTANOPSIS (FAGACEAE) - E. SOEPADMO; M. JACOBS (BRIN Publishing (Penerbit BRIN), 1968)
This paper deals with the names and typication of the 34 species recognized in Malesia. Specimens important for the knowledge of the distribution of each species have been cited with their locality. Indexes to names and to all examined specimens are given. Ten new species are described: Castanopsis clemensii, densinervia, endertii, microphylla,, oligoneura, oviformis, paucispina, peduneulata, psilophylla, all from Borneo, and johorensis from Malaya. C. hypophoenieea and C. lucida are new combinations based on Quercus hypophoenieea v. Seem, and Alseodaphne lucida Nees in Wall, respectively. Castanopsis ebneri and woodii are reduced to evansii, hullettii to lucida, pachycarpa to rhamnifolia, conspersispina, to tungurrut, dispersispina to hypophoenieea, ridleyi partly to tungurrut and partly to megacarpa, kinabaluensis to foxworthyi, pearsonii to mottleyana, junghuhnii and schlenkerae to acuniinatissima. Castanopsis selangorensis A. Cam. is regarded as a doubtful species. The number of endemic species is for Malaya 5, Borneo 11, the Philippines 1; the total number of species, is for Sumatra 11, Malaya 17, Java 4, Borneo 20, the Philippines 4, Celebes 2, the Moluccas 1, New Guinea 1, the Lesser Sunda Islands none.